Preferential Solvation Index as a Tool in the Analysis of the Behavior of Solvatochromic Probes in Binary Solvent Mixtures - Caroli-Rezende, M (Elsevier B.V., 2021)
The analysis of the solvation of a given solute is a puzzling phenomenon if the solute is placed in binary solvent mixtures. This is due to the preferential solvation (PS) of the solute by one of the solvents of the mixture. Solvatochromic dyes are used to describe binary solvent mixtures with different proportions of the components, from plots of molar transition energy (ET) values of a solvatochromic dye as a function of the mole fraction of the most polar solvent (X2) in the mixture. The quantitative analysis of these plots is commonly made by fitting the data using a quantitative solvent exchange model, with considerable success. However, although the fits are generally good, the results obtained are of difficult interpretation. Recently, a PS (or non–ideality) index (PSI) was introduced in an attempt to develop a simple tool for the qualitative and quantitative analysis of deviations from linearity verified in ET (dye) with X2 in mixtures of water with alcohols. Thus, it is necessary to extend the study related to the PSI to different probes and other solvent mixtures, to verify the advantages and limitations regarding the applications of this tool. Herein the solvatochromic behavior of five solvatochromic dyes in sixty–two binary solvent mixtures of a hydrogen–bond acceptor solvent (DMSO or acetonitrile) and a hydrogen–bond donor solvent (water and alcohols) was investigated. The PSI values were calculated and interpreted for each binary mixture. The comparison of PSIs for structurally different dyes in the binary mixtures provided interesting information about the solvation of the dyes. Thus, the analysis of the PSI values for the mixtures allow to interpret the phenomenon of PS not only in terms of a commitment of solute–solvent and solvent–solvent interactions, but also in terms of the intrinsic properties of the probe. © 2021 Elsevier B.V.